105 Integrated approach for controlling diseases and parasites in small ruminants: extension education and adoption. (5th December 2019) - Karki, Uma; Karki, Lila; Gurung, Nar
Abstract: Small-ruminant production is important farm enterprise in Alabama and other states of the Southeast, especially for small and limited-resource farmers. Poor health of animals caused by various diseases and parasites, resulting in a low performance is a major problem faced by most farmers. There are various strategies that can be adopted to minimize the prevalence of diseases and parasites and improve animal health. However, the majority of farmers are lacking the needed knowledge to adopt such strategies. The objective of this program was to educate farmers and extension educators on the integrated approach for controlling diseases and parasites in small ruminants. The program was initiated in 2010 and has been continued with training sessions (n = 7) conducted at the state level. County-level based programming (n = 22) has also been delivered in the form of hands-on training sessions and field days. Moreover, educational materials in the form of workshop proceedings (n = 1) and handouts, flyers, and fact sheets (n = 11) were developed and disseminated to the target audience and public through different outlets (county extension offices, training sessions, field days, farm visits, emails, blog, social media, web pages). Because of this program, numerous small-ruminant farmers and extension professionals are being trained every year (n = 40–51/yr.), and many more have access to educational materials (n = 1, 100–1, 700/yr.). Short-term impact evaluation of the program shows that knowledge and skills of the trainees have increased significantly (21–62%; P < 0.05). Trainees rated the presented topics useful (94%), they were very likely to implement what they learned (96%), and mentioned that such implementation would improve their farm situation (88%). Several trained farmers were found adopting the integrated approach and educators training their clientele on using the integrated approach to minimize health problems in small ruminants.